Biochar for soil health and crop production in the climate change era - Das, Shaon Kumar (Indian Farming, 2016)
Soil amendment with biochar has attracted a fair amount of researchinterest due to its abundant usage and wide potential, which includesenhancing crop production by improving soil fertility, decreasing green house gas emissions and increasing soil carbon sequestration. Use of biochar in agricultural systems is one viable option that can improve the soil quality, increase carbon sequestration in soil, reduce farm waste. However, to promote the application of biochar as a soil amendment and also as a climate change abatement option, research, development and demonstration on biochar production and application is very vital.